2018
DOI: 10.7196/sajch.2018.v12i2b.1524
|View full text |Cite
|
Sign up to set email alerts
|

Substance use among adolescents in sub-Saharan Africa: a systematic review and meta-analysis

Abstract: Substance use has become one of the growing major public health and socioeconomic issues worldwide; it has dramatically increased, particularly in developing countries. [1-3] The analysis of substance use is complex, due in part to its varieties, degree of secrecy, health challenges and different legal connotations surrounding its use globally. The use of khat (Catha edulis), cigarettes, heroine, alcohol and other substances is a worldwide threat which especially affects young people. The World Health Organiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
105
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(127 citation statements)
references
References 22 publications
16
105
6
Order By: Relevance
“…An accurate understanding of the drivers of substance use among adolescents is essential for the prevention and treatment of substance use and harmful use of alcohol, as enshrined in the Sustainable Development Goals (SDG3.5). The recent systematic review of substance use among adolescents in sub-Saharan Africa highlighted a prevalence of 41.6% [11]. Our study will build on this review with a focus on determinants, risk and protective factors in Africa [8].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…An accurate understanding of the drivers of substance use among adolescents is essential for the prevention and treatment of substance use and harmful use of alcohol, as enshrined in the Sustainable Development Goals (SDG3.5). The recent systematic review of substance use among adolescents in sub-Saharan Africa highlighted a prevalence of 41.6% [11]. Our study will build on this review with a focus on determinants, risk and protective factors in Africa [8].…”
Section: Discussionmentioning
confidence: 99%
“…A recently published systematic review found that the overall prevalence of 'any substance use' among adolescents in sub-Saharan African of 41.6%, with alcohol and tobacco being the highest prevailing substances (i.e. 40.8% and 45.6%, respectively) across the continent compared to any other substance use [11]. More interestingly, a few region-speci c patterns of substance use were identi ed, highlighting the need for region (or country) speci c and culturally appropriate interventions and policies.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Substance use is defined as the practice of using at least one of the substances such as alcohol, cigarettes, and licit or illicit drugs with the aim of enjoying the pleasurable effects of the psychoactive properties which comes with associated risks of addiction [1] Substance abuse on the other hand is defined as the harmful or hazardous use of psychoactive substances, including alcohol and/or illicit drugs in a manner that jeopardizes ones health despite knowledge of its dangers. Abuse, may be for both licit and illicit substances and may lead to substance use disorder (SUD) such as dependence which is a compulsive craving behaviour that persists despite known consequences [2] Substance use is a global problem causing 39 deaths per 100 000 population out of which 35 deaths are attributable to alcohol use while four are attributable to illicit drug [3] There is an emergent epidemic of tobacco, heroine and alchohol use among adoloscent in Sub-Saharan Africa (Olawole-Isaac, et al, 2018) with illegal substance consumption responsible for 37,000 people dying annually from illegal drug consumption related illnesses [4] The estimate of substance use among adolescents in Sub-Saharan Africa was found to be 41.6% (55 CI 31.3-51.9) with Central Africa taking the lead with 55.5% (95%-CI-53-58) followed by East Africa with 48.99%(95%-CI-28.8-69.2) and the least in Southern Africa at 37% (95% CI 16.1-57.8) [5] The Government of Kenya acknowledged substance abuse as a matter of national concern, and through a Legal Notice established the National Agency for Coordination of Drug & Substance abuse tasked with the responsibility to spearhead the campaign against substance use (NACADA, 2009). The Ministry of health indicate that the most commonly used drugs in Kenya are nicotine,alchohol and cannabis.…”
Section: Introductionmentioning
confidence: 97%